Joint constraints on galaxy bias and σ8 through the N-pdf of the galaxy number density. Issue 3 (4th March 2016) - Arnalte-Mur, Pablo; Vielva, Patricio; Martínez, Vicent J.; Sanz, José L.; Saar, Enn; Paredes, Silvestre
Abstract: We present a full description of the N-probability density function of the galaxy number density fluctuations. This N-pdf is given in terms, on the one hand, of the cold dark matter correlations and, on the other hand, of the galaxy bias parameter. The method relies on the assumption commonly adopted that the dark matter density fluctuations follow a local non-linear transformation of the initial energy density perturbations. The N-pdf of the galaxy number density fluctuations allows for an optimal estimation of the bias parameter (e.g., via maximum-likelihood estimation, or Bayesian inference if there exists any a priori information on the bias parameter), and of those parameters defining the dark matter correlations, in particular its amplitude ( σ8 ). It also provides the proper framework to perform model selection between two competitive hypotheses. The parameters estimation capabilities of the N-pdf are proved by SDSS-like simulations (both, ideal log-normal simulations and mocks obtained from Las Damas simulations), showing that our estimator is unbiased. We apply our formalism to the 7th release of the SDSS main sample (for a volume-limited subset with absolute magnitudes M r  ⩽ −20 ). We obtain b̂ = 1.193 ± 0.074 and σ̂8  = 0.862 ± 0.080, for galaxy number density fluctuations in cells of the size of 30 h −1 Mpc. Different model selection criteria show that galaxy biasing is clearly favoured.